Hubungan pola asuh orang tua dengan prestasi belajar siswa kelas IV sd negeri 2 pluneng - Maria Dian Anggraeni; Sri Marmoah; Sularmi Sularmi (Universitas Sebelas Maret, 2021)
In this research, the main problem that is taken is about the parenting style of the parents. This research aims to determine the effect of parenting style on student achievement. Respondents in this study were 20 fourth grade students from the Pluneng 2 Elementary School, Kebonarum District, Klaten Regency.This research is a quantitative correlation study. Data collection was carried out using test and non-test techniques. The test technique is used to test students' knowledge. While the non-test technique in the form of a questionnaire was used on the parenting style variable. Data were collected by distributing questionnaires to students. Data analysis used simple linear regression analysis. The final results in this research obtained a correlation coefficient of 0.000 <0.05, which means that there is a relationship between parenting styles and student achievement and the two variables have a strong relationship. In simple linear regression analysis, the equation Y = 8.428 + 0.797 X shows that learning achievement will increase by 0.797 units for every additional unit in the parenting style variable. In the t-test calculation, the results obtained, namely the Thit value of 4.775, greater than the T-table, which is 2,100. So it can be concluded that Ho is rejected and Ha is accepted which means that